HISTORIC APPROACHES ABOUT "BODY" (Fiep Bulletin - online, 2014)
This essay constitutive a approach of the understanding of the part culture Brazilian's Indians people into concept white men. The subject here is the esthetic between "Beauty", the Ugly and the "Savage" in its colors and punctual forms potential zed by surprise of the beauty art of the Antoine Watteau, so in the ornament and adornment witch in the exposition of the bodies, vestments, decorates, paints, non-mystified into nature, however, mythified into form of the romantic literature in the passage at century XIX to XX, in the transformation of the social canon of the cultural production.
Keywords: Art History; N. Elias; Jose de Alencar; Corporal Culture; Aesthetic